A clinical case and a review of Mycobacterium fortuitum infections direct diagnosis approach and treatment in a patient with leg fractures - Wang, Jun; Huang, Jing; Peng, Shijie; Li, Lianbao; Zhong, Kaijing; Chen, Taigui (The Journal of Infection in Developing Countries, 2022)
Mycobacterium fortuitum infections of the musculoskeletal system are commonly missed, given their rarity and the absence of systemic symptoms. In this study, we isolated the M. fortuitum from the skin sinus tract of a traffic accident patient's right medial knee surgical incision (over the open fracture wound), and confirmed by Morphological analysis, MALDI-TOF MS, 16S rRNA gene sequencing, and mNGS. Then we adjusted the treatment plan and treated the patient with cefoxitin, amikacin, and doxycycline. At three months follow-up review, his wound had completely healed. This report may provide a reference for the clinical treatment of Mycobacterium fortuitum infection in patients with open fractures.